A project to study and analyse the compatibility of Malaysian Laws with the International Convention for the Protection of all Persons from Enforced Disappearance (ICPPED) - Mohd Kamal, Mohd Hisham; Ab Hamid, Zuraini; Zul Kepli, Mohd Yazid (Human Rights Commission of Malaysia (SUHAKAM), 2022)
This project analysed the compatibility of Malaysian laws with the International Convention for The Protection of All Persons from Enforced Disappearance (ICPPED). Discussion includes the legal framework, best practice and lessens from ASEAN and OIC countries, related factors and implications.